Heart Failure with preserved ejection fraction: a pharmacotherapeutic update - Pedro Simão Vaz de Salvador (2022)
While guidelines for management of heart failure with reduced ejection fraction (HFrEF) are consensual and have led to improved survival, treatment options for heart failure with preserved ejection fraction (HFpEF) remain limited and aim primarily for symptom relief and improvement of quality of life. Due to the shortage of therapeutic options, several drugs have been investigated in multiple clinical trials. The majority of these trials have reported disappointing results and have suggested that HFpEF might not be as simply described by ejection fraction as previously though. In fact, HFpEF is a complex clinical syndrome with various comorbidities and overlapping distinct phenotypes that could benefit from personalized therapeutic approaches. This review summarizes the results from the most recent phase III clinical trials for HFpEF and the most promising drugs arising from phase II trials as well as the various challenges that are currently holding back the development of new pharmacotherapeutic options for these patients.